Technical challenges in generalizing calibration techniques for breast density measurements. Issue 2 (11th January 2019) - Fowler, Erin E. E.; Smallwood, Autumn M.; Khan, Nadia Z.; Kilpatrick, Kaitlyn; Sellers, Thomas A.; Heine, John
Abstract : Purpose: We are developing a calibration methodology for full‐field digital mammography (FFDM). Calibration compensates for image acquisition technique influences on the pixel representation, ideally producing improved inter‐image breast density estimates. This approach relies on establishing references with rigid breast tissue‐equivalent phantoms (BTEs) and requires an accurate estimate of the compressed breast thickness because the system readout is nominal. There is also an attenuation mismatch between adipose breast tissue and the adipose BTE that was noted in our previous work. It is referred to as the "attenuation anomaly" and addressed in this report. The objectives are to evaluate methods to correct for the compressed breast thickness and compensate for the attenuation anomaly. Methods: Thickness correction surfaces were established with a deformable phantom (DP) using both image and physical measurements for three direct x‐ray conversion FFDM units. The Cumulative Sum serial quality control procedure was established to ensure the thickness correction measurements were stable over time by imaging and calibrating DPs biweekly in lieu of physical measurements. The attenuation anomaly was addressed by evaluating adipose image regions coupled with an optimization technique to adjust the adipose calibration data. We compared calibration consistency across matched left and right cranial caudal (CC) mammographic views (n = 199) with and without corrections using Bland–Altman plots. These plots were complemented by comparing the right and left breast calibrated average (μa ) and population distribution mean (ma ) with 95% confidence intervals and difference distribution variances with the F‐test for uncorrected and corrected data. Results: Thickness correction surfaces were well approximated as tilted planes and were dependent upon compression force. A correction was developed for the attenuation anomaly. All paddles (large and small paddles for all units) exhibited similar tilt as a function of force. Without correction, ma  = 0.92 (−1.77, 3.62) was not significantly different from zero with many negative μa samples. The thickness correction produced a significant shift in the μa distribution in the positive direction with ma  = 13.99 (11.17, 16.80) and reduced the difference distribution variance significantly ( P  <   0.0001). Applying both corrections in tandem gave ma  = 22.83 (20.32, 25.34), representing another significant positive shift in comparison with the thickness correction in isolation. Thickness corrections were stable over approximately a 2‐year timeframe for all units. Conclusion: These correction techniques are valid approaches for addressing technical problems with calibration that relies on reference phantoms. The efficacy of the calibration methodology will require validation with clinical endpoints in future studies.